Numerical and experimental analysis of wake effect on tidal current turbine - Muhammad Shahrul, Sabri (2013)
The tidal current energy is one of the renewable energy existed on earth. Malaysia has the potential to develop a technology which can utilize this energy to generate electricity. The installation of marine current turbine array requires a deep research to maximize the potential energy of the sea current. Numerical and experimental investigation of tidal current energy extraction has been conducted in this study. Using commercial computational fluid dynamics (CFD) code ANSYS, the lab scale water flume was simulated. For the numerical model, tidal current turbine are represented by an actuator disk instead of scaled down turbine. The actuator disk produces a pressure drop which can be used to calculate the thrust coefficient. The turbulence kinetic energy and the velocity are closely monitored to investigate the wake effect produce. For experimental investigation, a 1m long, 0.2m high and 0.3m width of water channel fabricated. The same parameter which is velocity and turbulence effect downstream are closely monitored thus comparing the result with numerical simulation. Flowmeter is used to read the velocity of the current in the water channel. The result shown wake recover up to 70% at 4D for every numerical and experimental investigation.